The Influence of Implementation of a Review System on Employee Performance in Archives Management in PT. Industri Kapal Indonesia - Sitti Rajma; Nopian Siswahyudi (Universitas Negeri Makassar, 2021)
This study aims to determine the implementation of the filing system, employee performance, and the effect of the implementation of the filing system on employee performance in Archive Management at PT. Industri Kapal Indonesia (Persero) Makassar. The data obtained were processed using quantitative analysis designed in the form of a causal relationship (correlation). The population of this study was 155 people with a sample of 20 percent or 31 employees using the Simple Random Sampling technique. Data collection techniques used are observation, questionnaires, interviews, and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that the implementation of the archive system was in the good category in terms of five indicators, namely the creation of archives, management and control of archives, utilization of archives, maintenance of archives, and shrinkage of archives. For the performance of employees in managing archives, they are in a good category in terms of five indicators, namely quantity of work, quality of work, punctuality, attendance and ability to cooperate. The results of the analysis and hypothesis testing indicate that there is a positive and significant effect on the implementation of the filing system on employee performance in Archive Management at PT. Industri Kapal Indonesia (Persero) Makassar with a moderate level of influence. The results of the analysis and hypothesis testing indicate that there is a positive and significant effect on the implementation of the filing system on employee performance in Archive Management at PT. Industri Kapal Indonesia (Persero) Makassar with a moderate level of influence. The results of the analysis and hypothesis testing indicate that there is a positive and significant effect on the implementation of the filing system on employee performance in Archive Management at PT. Industri Kapal Indonesia (Persero) Makassar with a moderate level of influence